2020
DOI: 10.3390/brainsci10030140
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram (EEG) Alpha Power as a Marker of Visuospatial Attention Orienting and Suppression in Normoxia and Hypoxia. An Exploratory Study

Abstract: While electroencephalogram (EEG) alpha desynchronization has been related to anticipatory orienting of visuospatial attention, an increase in alpha power has been associated to its inhibition. A separate line of findings indicated that alpha is affected by a deficient oxygenation of the brain or hypoxia, although leaving unclear whether the latter increases or decreases alpha synchronization. Here, we carried out an exploratory study on these issues by monitoring attention alerting, orienting, and control netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Our findings, along with previous work, suggest that the initial alpha reduction indicates neural pathways are primed to detect and process incoming information, but then are fine-tuned to process salient information. This supposition, which is also discussed in similar work (Harquel et al, 2020;Pettorossi et al, 2013) is supported by work on the role of enhanced alpha as an inhibitory gating mechanism, one that facilitates attention by suppressing irrelevant information (Foxe & Snyder, 2011;Peng et al, 2015;Zani et al, 2020). In our paradigm, the asymmetric oscillations deliver conflicting stimulation in the form of fast versus slow rotation in opposite directions.…”
Section: Role Of Alpha Frequency Band In Adaptive Vestibular Perceptionsupporting
confidence: 75%
“…Our findings, along with previous work, suggest that the initial alpha reduction indicates neural pathways are primed to detect and process incoming information, but then are fine-tuned to process salient information. This supposition, which is also discussed in similar work (Harquel et al, 2020;Pettorossi et al, 2013) is supported by work on the role of enhanced alpha as an inhibitory gating mechanism, one that facilitates attention by suppressing irrelevant information (Foxe & Snyder, 2011;Peng et al, 2015;Zani et al, 2020). In our paradigm, the asymmetric oscillations deliver conflicting stimulation in the form of fast versus slow rotation in opposite directions.…”
Section: Role Of Alpha Frequency Band In Adaptive Vestibular Perceptionsupporting
confidence: 75%
“…Previous research on hypoxia has demonstrated a decline in cognitive function when oxygen's partial pressure goes below 50 mmHg [6]. In such cases, there is a decline in memory performance [7,8], attention skills [9], working memory [10], and executive functions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Through electroencephalography (EEG), it has been discovered that music directly influences brainwaves. Alpha EEG activity is the activity of the brain when at an awake but relaxed state (Zani et al, 2020). Pleasant music decreases alpha power in the left frontal lobe while unpleasant music decreases alpha power in the right frontal lobe.…”
Section: The Impact Of Music On the Brainmentioning
confidence: 99%